2014
DOI: 10.1371/journal.pgen.1004479
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Interacts with Bmp and Edn1 to Regulate Dorsal-Ventral Patterning and Growth of the Craniofacial Skeleton

Abstract: Craniofacial development requires signals from epithelia to pattern skeletogenic neural crest (NC) cells, such as the subdivision of each pharyngeal arch into distinct dorsal (D) and ventral (V) elements. Wnt signaling has been implicated in many aspects of NC and craniofacial development, but its roles in D-V arch patterning remain unclear. To address this we blocked Wnt signaling in zebrafish embryos in a temporally-controlled manner, using transgenics to overexpress a dominant negative Tcf3, (dntcf3), (Tg(h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 88 publications
(126 reference statements)
1
41
0
Order By: Relevance
“…In ventral cartilage development, Wnt signaling is required for early CNCC induction and later in CNCC migration, specification and proliferation by participating in a gene regulatory network with Edn1 and Bmp (Alexander et al, 2014). Heat-shock studies inhibiting Wnt through the overexpression of dkk1, a Wnt antagonist and dntcf3, a dominant negative form of the Tcf3 transcription factor, showed ventral patterning defects in the mandibular arch (Alexander et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ventral cartilage development, Wnt signaling is required for early CNCC induction and later in CNCC migration, specification and proliferation by participating in a gene regulatory network with Edn1 and Bmp (Alexander et al, 2014). Heat-shock studies inhibiting Wnt through the overexpression of dkk1, a Wnt antagonist and dntcf3, a dominant negative form of the Tcf3 transcription factor, showed ventral patterning defects in the mandibular arch (Alexander et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Heat-shock studies inhibiting Wnt through the overexpression of dkk1, a Wnt antagonist and dntcf3, a dominant negative form of the Tcf3 transcription factor, showed ventral patterning defects in the mandibular arch (Alexander et al, 2014). Recent studies using Wls to manipulate Wnt signaling, implicated its role in skeletal development by regulating osteogenesis and chondrogenesis (Maruyama et al, 2013; Rochard et al, 2016; Zhong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the search results, previous studies showed that Wnt/ß‐catenin induces BMP/EDN1 as well as TGFß3 expression, important for ventralizing patterning and mesenchymal differentiation, whereas BMP and FGF induce SOX9 and SOX10, which are responsible for chondrogenic activation (Alexander et al, ; Jayasena and Bronner, ; Jin et al, ). Previous studies on regulatory pathways showed that TGFß and BMP signaling induce and control osteogenic gene expression (Gu et al, ; He et al, ; Jayasena and Bronner, ; Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…8D). Arch patterning occurs between 20 and 30-36 hpf, when pharyngeal arch mesenchyme is divided into major domains by signaling and transcription factors (Alexander et al, 2014; Miller, 2003; Miller et al, 2000; Nichols et al, 2013; Talbot et al, 2010; Zuniga et al, 2010). During this same phase, early endodermal pouch-1 forms (Schilling and Kimmel, 1994) and is a rich source of patterning signals (Choe and Crump, 2015).…”
Section: Discussionmentioning
confidence: 99%